Waste segregation and processing training at Lenterahati Islamic Boarding School (LHIBS) West Lombok - Joni Safaat Adiansyah; Nurhayati Nurhayati; Ibrahim Ibrahim; Sukuryadi Sukuryadi; Harry Irawan Johari; Aryan Perdana Putra (Community Empowerment, 2023)
As an island that well knowns as the island of a thousand mosques, the existence of Islamic boarding schools on Lombok Island is commonplace. With its existence, of Islamic boarding schools could be classified as one of the sources of waste generation. Lenterahati Islamic Boarding School (LHIBS) is one of the Islamic Boarding Schools in West Lombok Regency which has been made as a partner in the community service activities. The main goal is to increase the Islamic school student understanding of waste types and the effective waste management strategies. Two methods were applied, namely Focus Group Discussion (FGD) and composting training. The result achieved is an increase in students' understanding and skills in composting. This also means that there is a reduction in the amount of waste that is disposed of at the Final Disposal Site.